Developing Student Worksheet of Temperature and Heat Based on Scientific Process Skill - Fhadhila, Fharia; Ertikanto, Candra; Rosidin, Undang (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
This research aims to develop a product in the form of Student Worksheet of temperature and heat based on Scientific Process Skills. The study was conducted within five stages: analysis, design, development, implementation, and evaluation. The results of the research showed that Student Worksheet’s construct validity value of 80.30% and 70.96% of content validity. Student Worksheet has a questionnaire value of easiness of 3, 29, attractiveness of 3.32 and usefulness of 3.19. Student Worksheet effectively increases the average of the students’ learning outcomes both in the cognitive domain of 80.00, affective domain of 81.30% and psychomotor domain of 80.81. Based on the results of the research, it can be said that Student Worksheet achieved the goal of characteristics development i.e., possesses content validity and construct validity in the good category, user feedback questionnaire with the result of very easy to use, highly attractive and helpful, and the effectiveness of increasing the average students’ learning outcomes in the very high category. For future studies, the researchers suggest that the Science Process Skill-based worksheets are not only applied to the temperature and heat material but can be applied to other branches of science